ANTIBACTERIAL ACTIVITY OF ARECA NUT SOAP FORMULATION AGAINST STAPHYLOCOCCUS AUREUS - Rahman, Ave Olivia; Purwakanthi, Anati (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2021)
ABSTRACTBackground: Areca nuts are widely grown in Jambi and areca seeds have antibacterial activity, antioxidant, skinaging and cosmetics. It has the potential to be developed as antibacterial soap.Objective: This study was to compare the antibacterial effect of betel nut concentration powder and extract in oursoap formulation against Staphylococcus aureus using the in vitro test.Method: Soap formulation was made with 3 concentration of areca nut powder in soap, namely 1,5 grams/soap(soap 1); 2,3 grams/soap (soap 2) and 3 grams/soap (soap 3). also with extract of areca nut 1,2 grams/soap (soap4). The final weight of soap was obtained 50 grams. Antiseptic soap brand X and Y as a control. Antibacterialactivity test using Staphylococcus aureus ATCC 25923 with the well method.Results: The diameter of the clear zone produced by each areca nut soap was not much different (p>0,05). Theclear zone diameter of soap 1, 2, 3 and 4 were 24.28 ± 7,95 mm, 23,96 ± 6,41 mm, 23,87 ± 6,14 mm, and 23,08± 1,52 mm respectively. While, diameter of clear zone in brand X and Y were zero. Conclusion: The betel nutsoap formulation in this study has better antibacterial activity against Staphylococcus aureus ATCC 25923 thancontrol.Keywords: soap, areca nut, antibacterial, Staphylococcus aureusABSTRAKLatar Belakang: . Pohon pinang banyak ditanam di Jambi dan biji pinang memiliki aktivitas antibakteri, antioksidan,anti penuaan dan kosmetik. Biji pinang berpotensi untuk dikembangkan sebagai sabun antibakteri.Tujuan: Penelitian ini membandingkan efek antibakteri sabun pinang dengan bahan aktif dalam bentuk serbukdan eksktrak terhadap Staphylococcus aureus menggunakan uji in vitro.Metode: Formulasi sabun dibuat dengan 3 kadar serbuk pinang dalam sabun, yaitu 1,5 gram / sabun (sabun 1);2,3 gram / sabun (sabun 2) dan 3 gram / sabun (sabun 3), serta ekstrak biji pinang 1,2 gram/sabun. Berat akhirsabun diperoleh 50 gram. Sabun antiseptik merek X dan Y sebagai kontrol. Uji aktivitas antibakteri menggunakanStaphylococcus aureus ATCC 25923 dengan metode sumur.Hasil: Diameter zona bening yang dihasilkan masing-masing sabun pinang tidak jauh berbeda (p>0,05). Diameterzona bening sabun 1, 2 , 3 dan 4 masing-masing adalah 24.28 ± 7,95 mm, 23,96 ± 6,41 mm, 23,87 ± 6,14 mm,dan 23,08 ± 1,52 mm. Sedangkan diameter zona bening pada merek X dan Y adalah nol. Kesimpulan: Formulasisabun pinang pada penelitian ini memiliki aktivitas antibakteri yang lebih baik terhadap Staphylococcus aureusATCC 25923 daripada sabun control.Kata kunci: sabun, pinang, antibakteri, Staphylococcus aureus